Odpowiedzi

2010-02-16T11:50:09+01:00
A) 7x2 − 4x − 6x2 + 4 − x2 + 5x =
x+4
b) −2(3a − 2b) − 4a(2 − 3a + 2b) =
-6a+4b-4a+3a2-8ab=
-10a+4b-3a2-8ab
c) (4 − x)(2x + 5) − 4 =
8x+20-2x2-5x-4=
3x+16-2x2
d) (4 − 2x)(3x − 3) − 2x(3x + 1) =
12x-12-6x2+6x-6x2-2x=
16x-12-12x2



mam nadzieje ze pomoglam
pozdrawiam. ;)
7 1 7
2010-02-16T11:51:43+01:00
A) 7x² − 4x − 6x² + 4 − x² + 5x =x+4
b) −2(3a − 2b) − 4a(2 − 3a + 2b) =-6a+4b-8a+12a²-8ab=-14a+4b+12a²-8ab
c) (4 − x)(2x + 5) − 4 =8x+20-2x²-5x-4=3x+16-2x²
d) (4 − 2x)(3x − 3) − 2x(3x + 1) =12x-12-6x²-6x-6x²-2x=4x-12x²-12
10 3 10
Najlepsza Odpowiedź!
2010-02-16T14:57:13+01:00
A)
7x2 − 4x − 6x2 + 4 − x2 + 5x = x+4
b)
−2(3a − 2b) − 4a(2 − 3a + 2b) = -6a+4b-8a+12a²-8ab = -14a+4b+12a²-8ab
c)
(4 − x)(2x + 5) − 4 = 8x+20-2x²-5x-4 = 3x+16-2x²
d)
(4 − 2x)(3x − 3) − 2x(3x + 1) = 12x-12-6x²+6x-6x²-2x = 16x-12-12x²
9 4 9